Mitigating Racial and Sex Disparities in Access to Living Donor Kidney Transplantation: Impact of the Nation's Longest Single-center Kidney Chain. Issue 4 (October 2019) - Mustian, Margaux N.; Kumar, Vineeta; Stegner, Katie; Mompoint-Williams, Darnell; Hanaway, Michael; Deierhoi, Mark H.; Young, Carlton; Orandi, Babak J.; Anderson, Douglas; MacLennan, Paul A.; Reed, Rhiannon D.; Shelton, Brittany A.; et al.
Abstract : Objective: In this study, we sought to assess likelihood of living donor kidney transplantation (LDKT) within a single-center kidney transplant waitlist, by race and sex, after implementation of an incompatible program. Summary Background Data: Disparities in access to LDKT exist among minority women and may be partially explained by antigen sensitization secondary to prior pregnancies, transplants, or blood transfusions, creating difficulty finding compatible matches. To address these and other obstacles, an incompatible LDKT program, incorporating desensitization and kidney paired donation, was created at our institution. Methods: A retrospective cohort study was performed among our kidney transplant waitlist candidates (n = 8895). Multivariable Cox regression was utilized, comparing likelihood of LDKT before (era 1: 01/2007–01/2013) and after (era 2: 01/2013–11/2018) implementation of the incompatible program. Candidates were stratified by race [white vs minority (nonwhite)], sex, and breadth of sensitization. Results: Program implementation resulted in the nation's longest single-center kidney chain, and likelihood of LDKT increased by 70% for whites [adjusted hazard ratio (aHR) 1.70; 95% confidence interval (CI), 1.46–1.99] and more than 100% for minorities (aHR 2.05; 95% CI, 1.60–2.62). Improvement in access to LDKT was greatest among sensitized minority women [calculated panel reactive antibody (cPRA) 11%–49%: aHR 4.79; 95% CI, 2.27–10.11; cPRA 50%–100%: aHR 4.09; 95% CI, 1.89–8.82]. Conclusions: Implementation of an incompatible program, and the resulting nation's longest single-center kidney chain, mitigated disparities in access to LDKT among minorities, specifically sensitized women. Extrapolation of this success on a national level may further serve these vulnerable populations.